2021
DOI: 10.1038/s41467-021-21841-w
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 couples cyst(e)ine availability with GPX4 protein synthesis and ferroptosis regulation

Abstract: Glutathione peroxidase 4 (GPX4) utilizes glutathione (GSH) to detoxify lipid peroxidation and plays an essential role in inhibiting ferroptosis. As a selenoprotein, GPX4 protein synthesis is highly inefficient and energetically costly. How cells coordinate GPX4 synthesis with nutrient availability remains unclear. In this study, we perform integrated proteomic and functional analyses to reveal that SLC7A11-mediated cystine uptake promotes not only GSH synthesis, but also GPX4 protein synthesis. Mechanistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
310
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 448 publications
(323 citation statements)
references
References 75 publications
13
310
0
Order By: Relevance
“…However, it remains unclear whether kaempferol suppresses OGD/R-induced ferroptosis. GPX4 is very important for regulating ferroptosis and SLC7A11 acts as an upstream mediator of GPX4 [22]. In addition, Nrf2 can inhibit ferroptosis via regulation of SLC7A11 [10,23].…”
Section: Kaempferol Activates Slc7a11 Gpx4 and Nrf2 In Ogd/r-treated Neuronsmentioning
confidence: 99%
“…However, it remains unclear whether kaempferol suppresses OGD/R-induced ferroptosis. GPX4 is very important for regulating ferroptosis and SLC7A11 acts as an upstream mediator of GPX4 [22]. In addition, Nrf2 can inhibit ferroptosis via regulation of SLC7A11 [10,23].…”
Section: Kaempferol Activates Slc7a11 Gpx4 and Nrf2 In Ogd/r-treated Neuronsmentioning
confidence: 99%
“…Cystine uptake using [ 14 C]cystine (Perkin Elmer) was conducted as described previously (Zhang et al, 2018(Zhang et al, , 2021. Glucose uptake was conducted similar to cystine uptake.…”
Section: Cystine and Glucose Uptake Assaysmentioning
confidence: 99%
“…However, this simple view was challenged by the observation that GSH depletion generally induces much milder ferroptotic cell death than does cystine starvation or class 1 FIN treatment, or even fails to cause significant cell death in certain cancer cell lines, [51] raising the question of whether the anti-ferroptosis role of SLC7A11-mediated cystine uptake involves other unknown mechanisms. A recent study by Zhang et al partly fills in this knowledge gap by showing that cyst(e)ine promotes not only GSH synthesis but also GPX4 protein synthesis through the Rag-mTORC1-4EBP signaling pathway [46] (Figure 2A). In that study, proteomic analyses revealed that GPX4 protein level was significantly downregulated upon cystine starvation, which was further confirmed by either erastin treatment or SLC7A11 knockdown.…”
Section: Mtorc1 Mediates Cyst(e)ine-induced Gpx4 Protein Synthesismentioning
confidence: 99%
“…Notably, a series of recent studies revealed intriguing interplays between mTORC1 signaling and ferroptosis. [46][47][48][49] In the following sections, we summarize these recent findings linking mTORC1 to ferroptosis, analyze the seemingly context-dependent role of mTORC1 in either suppressing or promoting ferroptosis, and discuss the potential of combining mTORC1 inhibitors and FINs in cancer therapy.…”
Section: Instead Incorporation Of Mufas Into Pls Can Displace Pufas Frommentioning
confidence: 99%
See 1 more Smart Citation